The use of MRFA as an adjunct to conventional clinical examination following peri-implantitis treatment. A 12 month follow up. - Madeley, Edward (Trinity College Dublin, School of Dental Sciences, Dental Science, 2019)
Aim: The aims of the present study were to investigate the impact of peri-implantitis treatment upon periodontal clinical parameters and implant stability quotient values. To ascertain if magnetic resonance frequency analysis (MRFA) can be used as a diagnostic tool to demonstrate post operative healing following treatment of peri-implantitis; and to identify the most appropriate time for re-evaluation of implant stability. Materials and Methods: Patients were sampled from a cohort of patients with peri-implantitis, referred or presenting to Dublin Dental University Hospital. Prostheses of diseased implants were dismantled at baseline and periodontal diagnostic parameters were taken (PPD, CAL, BoP, Plaque score). Baseline MRFA levels were taken with an Osstell™ device, in addition to baseline radiographs prior to any treatment. Patients were treated in accordance with the severity of their disease. All patients received non-surgical therapy following baseline examination; surgical and regenerative therapy was provided where suitable. Post baseline therapy, patients were reassessed at 3, 6 and 12 months and all clinical parameters repeated in addition to MRFA measurements; with the exception of 3 months probing where regenerative surgery was carried out. Radiographs were repeated at 12 months. Results: 18 patients were enrolled in the study with 57 implants treated for peri-implantitis. All mean tested clinical periodontal diagnostic parameters showed a statistically significant improvement in the 12 months post-initial therapy without exception. There was a trend for increasing mean implant stability quotient (ISQ) levels over 12 months which was not significant. There was a statistically significant correlation between changes in all tested mean periodontal parameters and changes in ISQ levels over 12 months with the exception of plaque and bleeding on probing scores which showed no significant correlation. Conclusions: Overall, in the medium to short term, all treatments were successful in the management of peri-implantitis. When sub-analysis was carried out based on treatment provided, implants treated surgically with GTR or GBR achieved better clinical results (as evidenced by PD reduction and bone gain) and showed more frequent correlations with MRFA readings. MRFA technology, in the form of the Osstell™ device, can be used as a complement to the commonly used periodontal tools for the evaluation of post operative implant stabilty following treatment of peri-implant disease.
Keywords: Peri-implantitis; Magnetic resonance frequency analysis